FT IR STUDY OF INTERACTION OF VITAMIN D$_2$ WITH DIMETHYLSULFOXIDE AND DIETHYLSULFOXIDE (Proceedings of the YSU B: Chemical and Biological Sciences, 2010)
The complex formation between Vitamin D2 and dimetylsulfoxide (DMSO) and diethylsulfoxide (DESO) in tetrachloromethane has been studied on the basis of FT IR spectroscopic measurements. The results obtained show that complex formation between Vitamin D2 and sulfoxide occurs through hydrogen bond of the type O–H...O=S. The equilibrium constants of Vitamin D2–DMSO and Vitamin D2–DESO complexes were determined at 23 oC.
Keywords: Vitamin D2; dimetylsulfoxide; diethylsulfoxide; tetrachloromethane